IPTEKS PENGAKUAN DAN PENGUKURAN PENDAPATAN PREMI ASURANSI PADA PT JASA RAHARJA (PERSERO) CABANG SULAWESI UTARA - Prihatanto, Candra Rizky; Mintalangi, Syermy S.E. (Universitas Sam Ratulangi, 2018)
PT Jasa Raharja is a company who handles about social insurance, where at the end of each accounting period year, will make and report a financial statement. In company’s financial statement, revenue is an important component. One of the existing income of PT Jasa Raharja is insurance premium income. The purpose of the writer is to compare and to gain knowlegde whether company’s account treatment of insurance premium income already in accordance with the existing accounting standard, especially in recognition and measurement of insurance premium income. The accounting treatment of company’s insurance premium income must be controlled as to prevent misinformation in company’s financial statement.Keywords: accounting standard, insurance premium income